Wavelet based performance analysis of AC transmission systems with unified power flow controller under power quality issues - M. Nagaraju; V. V. K. Reddy; M. Sushama (International Journal of Applied Power Engineering (IJAPE), 2019)
The developments in power quality are fast and difficult to predict. The majority of power quality issues experienced by industrial customers can be attributed to momentary interruptions, voltage sags or swells, transients, harmonic distortion, electrical noise, and flickering lights, among others. A new device may be invented tomorrow solving power quality problems. The FACTS devices could provide fast control of active and reactive power through a transmission line. The unified power-flow controller (UPFC) is a member of the FACTS family with very attractive features. This device can independently control many parameters, so it is the combination of the properties of a static synchronous compensator (STATCOM) and static synchronous series compensator (SSSC).The performance of AC Transmission system with Unified power flow controller under various power quality problems analysis described. The proposed system is formulated and research work is done by wavelet multi resolution analysis using Bior1.5 mother wavelet with MATLAB/SIMULINK software. It is observed that the effectiveness of AC power transmission through Unified power flow controller under power quality problems of sag, swell, transient, temporary faults and capacitive switching.